PROTOTYPE LAMPU PENERANGAN JALAN OTOMATIS BERDASARKAN SENSOR CAHAYA BERBASIS ARDUINO PADA DESA BUKIT HARAPAN KECAMATAN GANTARANG KABUPATEN BULUKUMBA - Ayu Reski (LPPM STMIK BINA ADINATA, 2020)
This research to: (1) Design a street lighting lamp automatically using Arduino and LDR sensors. (2) Connect Arduino and LDR sensors. (3) Implement solar panels as an energy source in the prototype of an automatic street lighting.This research uses the Action Research method which is one of the problem solving strategies in which the researcher describes and explains a social situation at the same time to make changes with the aim of repairing, improving and developing the system or situation. This method has the following rare steps: (1) Planning (2) Action, (3) Observation, (4) Reflection.Based on the test results it can be concluded that by using, the Arduino Uno microcontroller as the central control circuit and programmed using the Arduino IDE software, coupled with LDR sensors and solar panels as an energy source, it can create street lighting that automatically turns on and goes out when the LDR sensor detects the light intensity in accordance with the value of the intensity of the flame light and light outages that have been specified in the Arduino IDE program. This tool is very useful for street lighting that still uses the On / Off switch, because the tool is very effective and can work by itself.